2004
DOI: 10.1262/jrd.50.1
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Regulation of Expression of Luteinizing Hormone Receptor in the Ovary and the Mechanism of Follicular Cyst Formation in Ruminants

Abstract: Abstract. In the series of studies, changes of expression and regulation of luteinizing hormone (LH) receptor in the ovary of domestic ruminants were examined. Furthermore, mechanisms of formation of follicular cysts in domestic ruminants, caused by stress and so on, were endocrinologically elucidated. Results of the studies provide the following conclusions. (1) The quantity of LH receptor in the bovine antral follicles increases rapidly in the latter stage of its development. (2) The quantity of LH receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
(55 reference statements)
2
15
0
2
Order By: Relevance
“…Finally, ovulation does not occur and the follicle becomes cystic. This proposed mechanism agrees with the decreased expression of LHCGR reported both by Kawate (2004) and our group (Marelli et al 2014).…”
Section: Expression Of Gonadotropin Receptorssupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, ovulation does not occur and the follicle becomes cystic. This proposed mechanism agrees with the decreased expression of LHCGR reported both by Kawate (2004) and our group (Marelli et al 2014).…”
Section: Expression Of Gonadotropin Receptorssupporting
confidence: 92%
“…The gene encoding LHCGR contains 11 exons (Segaloff et al 1990, Segaloff & Ascoli 1993, while that encoding FSHR contains ten exons (Rajapaksha et al 1996, Hillier 2001. It has also been demonstrated that LHCGR and FSHR mRNAs are highly alternatively spliced (Figs 1 and 2; Rajapaksha et al 1996, Simoni et al 1997, Robert et al 2003, Kawate 2004, Nogueira et al 2010. However, there are no investigations of splice variants in ovarian follicular cysts.…”
Section: Expression Of Gonadotropin Receptorsmentioning
confidence: 98%
“…Previous studies have shown that the variants with a partial deletion of exon 11 are translated into protein, but are not translocated to the cell membrane and instead become intracellularly trapped (Kawate, 2004). Thus, if these mRNAs are translated they are unable to bind LH and cannot activate adenylyl cyclase.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological conditions, testosterone is almost exclusively (>95%) of testicular origin (Wilson et al, 1981). Thus, the quality and quantity of LHR are important factors affecting the sensitivity to its ligand (Kawate, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation